How does community health feature in Global Financing Facility planning documents to support reproductive, maternal, newborn, child and adolescent health and nutrition (RMNAH-N)? insights from six francophone West African countries - Joël Arthur Kiendrébéogo; Orokia Sory; Issa Kaboré; Yamba Kafando; Rosie Steege; Asha S. George; Meghan Bruce Kumar (Global Health Action)
Background Community health is key for improving Reproductive, Maternal, Newborn, Child, and Adolescent Health and Nutrition (RMNCAH-N). However, how community health supports integrated RMNCAH-N service delivery in francophone West Africa is under-researched. Objective We examined how six francophone West African countries (Burkina Faso, Côte d’Ivoire, Guinea, Mali, Niger, and Senegal) support community health through the Global Financing Facility for Women, Children and Adolescents (GFF). Methods We conducted a content analysis on Investment Cases and Project Appraisal Documents from selected countries, and set out the scope of the analysis and the key search terms. We applied an iterative hybrid inductive-deductive approach to identify themes for data coding and extraction. The extracted data were compared within and across countries and further grouped into meaningful categories. Results In country documents, there is a commitment to community health, with significant attention paid to various cadres of community health workers (CHWs) who undertake a range of preventive, promotive and curative roles across RMNCAH-N spectrum. While CHWs renumeration is mentioned, it varies considerably. Most community health indicators focus on CHWs’ deliverables, with few related to governance and civil registration. Challenges in implementing community health include poor leadership and governance and resource shortages resulting in low CHWs performance and service utilization. While some countries invest significantly in training CHWs, structural reforms and broader community engagement are lacking. Conclusions There is an opportunity to better prioritize and streamline community health interventions, including integrating them into health system planning and budgeting, to fully harness their potential to improve RMNCAH-N.